Culture and education in the Zuckerberg galaxy: reflections from children and juvenile’s diary (Journal of the Sociology and Theory of Religion, 2019)
The present article elaborates reflects on the configuration of the present time, that will be considered as "Galaxy of Zuckerberg" (and not only the "global village" of McLuhan). After the galaxies of Gutenberg (editorial massification) and Marconi (speed of diffusion), we are living a time of profound changes in the means and in the processes of communication, which are generating social, cultural and educational transformations. Starting from the confrontation of a wide range of approaches (Popper, Llosa, Lipovetsky, Bauman, Melo, Nichols, Foer, Valero-Matas, Sánchez-Bayón, among others), we reflect on culture in the post-globalization era, marked by virtualization and dematerialization of ways of living and communicating. In the context of literary semiotics, an analysis of diaristic works of children and teens' literature is made, highlighting the process of fictionalization of this autobiographical genre and the investment in humor narratives, marked by the unsacredness (ethical problem) of relations - with obvious repercussions in the field of education.
Keywords: Galaxy of Zuckerberg; culture; education; children and juvenile’s literature; diary.